2008
DOI: 10.1128/iai.00744-07
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Mechanisms of EntericHeligmosomoides polygyrusInfection against Trinitrobenzene Sulfonic Acid-Induced Colitis in a Murine Model

Abstract: Recent studies showed that enteric helminth infection improved symptoms in patients with inflammatory bowel disease as well as in experimental models of colitis. The aim of this study was to determine the mechanism of the protective effect of helminth infection on colitis-induced changes in immune and epithelial cell function. BALB/c mice received an oral infection of Heligmosomoides polygyrus third-stage larvae, were given intrarectal saline or trinitrobenzene sulfonic acid (TNBS) on day 10 postinfection, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 66 publications
2
51
2
Order By: Relevance
“…These observations are supported by the results showing that intestinal helminth infection increases the intestinal translocation/ absorption of bacterial products such as lipopolysaccharide (LPS) into the portal circulation by altering barrier function (10) and that IL-4 treatment of keratinocytes significantly enhanced the permeability to high-molecular-mass material (40-kDa fluorescein isothiocyanate [FITC]-dextrans) through modification of intercellular adhesion molecules (23). In contrast, a recent study that used an Ussing chamber approach measured mucosal permeability and secretion ex vivo and showed that H. polygyrus infection increased colonic mucosal resistance (34). The differences in helminth-induced colonic permeability between this report (34) and our current study may be due to the differences in the experimental approaches used.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These observations are supported by the results showing that intestinal helminth infection increases the intestinal translocation/ absorption of bacterial products such as lipopolysaccharide (LPS) into the portal circulation by altering barrier function (10) and that IL-4 treatment of keratinocytes significantly enhanced the permeability to high-molecular-mass material (40-kDa fluorescein isothiocyanate [FITC]-dextrans) through modification of intercellular adhesion molecules (23). In contrast, a recent study that used an Ussing chamber approach measured mucosal permeability and secretion ex vivo and showed that H. polygyrus infection increased colonic mucosal resistance (34). The differences in helminth-induced colonic permeability between this report (34) and our current study may be due to the differences in the experimental approaches used.…”
Section: Discussionmentioning
confidence: 93%
“…4). These (12), which may alter the host response to other pathogens or antigens (13,20,31,32,34). To directly demonstrate the role of the adaptive immune system in the immune modulation of colonic epithelial barrier function during intestinal helminth infection, we next adoptively transferred unfractionated lymphocytes isolated from the spleens and lymph nodes of normal BALB/c mice into SCID mice, which were infected with 200 third-stage H. polygyrus larvae or left uninfected.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that the H. polygyrus life cycle takes place in the intestine (without entering the circulation), the parasite potently modulates systemic immune responses. It has been investigated in many animal models of inflammatory disease, including T1D, colitis, allergy, asthma, and gastric atrophy [39,[41][42][43][44][45][46][47][48] + T cells via ligation of the host TGF-β receptor [49].…”
Section: Abbreviationsmentioning
confidence: 99%
“…This protective effect could also be adoptively transferred with either regulatory T (Treg) cell [31], or B-cell transfer [32], in both cases in an IL-10 independent manner. Together with a number of other studies on H. polygyrus infection in allergy [33,34], colitis [35][36][37] and diabetes [38,39], it is clear that this helminth downregulates multiple effector pathways of the adaptive immune response [40].Therapy of human immune pathologies with live helminth parasites continues to be evaluated, but will remain an empirical process. Moreover, permitted doses of live parasites are minimal due to ethical and logistical constraints [41], such that exposure levels and duration do not approach those seen in endemic populations.…”
mentioning
confidence: 99%